The Implications of British Colonial Territorial Division on Class Conflict in India and Pakistan - Maharani, Citra Ayu; Walalangi, David Rivendell (Padjadjaran Journal of International Relations, 2026)
This article examines how British colonial practices in India, including determining territorial boundaries, shaped power relations and class structures that were later reproduced into modern geopolitical conflict. The theoretical framework employed is Geopolitical Marxism, which emphasizes that relations of ownership and control over resources are the primary drivers of social and political change. This research adopts a qualitative method. The data are derived from secondary sources collected from various relevant materials. The collected data are then sorted and categorized according to the research focus. Subsequently, the data are analyzed using cross-source data triangulation to ensure the validity of findings and to strengthen the accuracy of interpretative results. The findings indicate that the hasty and arbitrary division of territory, such as the establishment of the Radcliffe Line, reinforced socio-economic inequalities and opened space for power struggles among postcolonial political elites. The prolonged conflicts in Punjab, Bengal, and Kashmir represent the reproduction of colonial ruling-class formations within modern state structures. The legacy of British colonialism is therefore not limited to territorial boundaries, but also includes enduring class domination that continues to generate cycles of conflict in India-Pakistan today.Penelitian ini membahas bagaimana praktik kolonial Inggris di India, termasuk dalam penentuan batas teritorial, membentuk relasi kekuasaan dan kelas yang kemudian direproduksi menjadi konflik geopolitik modern. Kerangka teori yang digunakan adalah Geopolitical Marxism yang menekankan bahwa relasi kepemilikan dan penguasaan sumber daya adalah penggerak utama perubahan sosial dan politik. Penelitian ini menggunakan metode kualitatif. Data penelitian diperoleh melalui data sekunder yang dikumpulkan dari berbagai sumber relevan. Data yang telah terkumpul kemudian dipilah dan dikategorikan sesuai dengan fokus penelitian. Selanjutnya, data dianalisis menggunakan teknik triangulasi data antar sumber untuk memastikan validitas temuan dan memperkuat ketepatan interpretasi hasil penelitian. Temuan penelitian menunjukkan bahwa pembagian wilayah yang tergesa-gesa dan arbitrer, seperti penetapan Radcliffe Line, memperkuat ketimpangan sosial-ekonomi dan membuka ruang bagi perebutan kekuasaan antar elit politik pascakolonial. Konflik berkepanjangan di Punjab, Bengal, dan Kashmir merupakan hasil reproduksi kelas penguasa kolonial ke dalam struktur negara modern. Warisan kolonial Inggris tidak hanya berupa batas teritorial, tetapi juga struktur dominasi kelas yang terus menciptakan siklus konflik di India-Pakistan hingga saat ini.